La metodología montessori y su relación en el desarrollo cognitivo de los niños y niñas de tercer grado del subnivel de básica elemental, de la escuela de educación básica “IV Centenario no. 1” de la ciudad de Loja, período académico 2012- 2013 - Benítez Cuenca, Estrella del Cisne (2014)
The research related to the topic: THE MONTESSORI METHOD AND ITS RELATIONSHIP IN COGNITIVE DEVELOPMENT OF CHILDREN OF THIRD GRADE sublevel BASIC ELEMENTARY SCHOOL BASIC EDUCATION "CENTENNIAL IV NO. 1 "CITY Loja, ACADEMIC YEAR 2012- 2013 whose aim was to investigate the relationship of the Montessori approach to cognitive development in children sublevel Third Grade Basic Elementary, School of Basic Education" IV Centenario No. 1 "of the city of Loja. Which specific objectives were derived: teachers encourage the acquisition of knowledge about the Montessori method, where the child can do to develop their skills within a structured program that will be attractive and motivated environment; know the different stages of cognitive development and differentiate in order to identify the benefits it can provide us; and propose alternative guidelines in order that teachers know and aptly employ the Montessori Methodology applied to cognitive development. The methodology used is qualitative in nature, since it corresponds to the descriptive research court. This required the use of methods such as: Scientific Method, the Descriptive Method; Analytical Method - Synthetics, as well as techniques such as survey and the instruments that were applied as in the questionnaire, which were applied to teachers and students respectively. In each of the sequences, according to the development schedule of the activities that made it possible to systematize and analyze the results had planned, for which the participation of the following human talent was needed 6 teachers and 54 students. After processing the information, it was established as conclusions that teachers maintain that the material used is the blackboard, posters and books to use during class. Teachers argue that they should disclose the values of respect, punctuality, responsibility and honesty. So it is recommended that school authorities to socialize with teachers the right material to exhibit during class; the entire faculty to plan related to the above values, and while these can be put to practical activities. Given the above developed an alternative that allows the proper orientation for teachers and teachers of Basic General Education "School No. IV Centenario. 1 "of the city of Loja, know the Montessori methodology, its importance in the overall education of students and their close relationship to cognitive development since today is very clear that education is a vital role in the formation the human being.